Sifat-sifat Tarik dan Flexural Komposit Serat Sabut Kelapa Unidireksional/Poliester - Sudarisman, Sudarisman; Kamiel, Berli P; Rahadi, Slamet (Semesta Teknika, 2014)
The purpose of this study is to investigate the tensile and flexural properties of unidirectional coconut fiber/polyester composite materials, and to describe their failure modes. Specimens were cut from fiber/polyester composite plates containing various fiber contents. Materials being used in this study are coconut fiber that was previously alkali-treated and polyester resin matrix. Whilst tensile testing was carried out in accordance with the ASTM D3039 standard, flexural testing was based on the ASTM D790 standard. Failure surfaces of the representative specimens were then observed under an optical microscope, and their digital photo macrographs were captured for image analysis in order to describe their respective fiber distribution pattern and to determine their respective actual fiber volume fraction, Vf, by means of an open source software called ImageJ. It was found out that the actual Vf of the four composite plates being produced were 10.7%, 17.6%, 27.4% and 40.5%. It was revealed that while tensile strength increases with the increase of Vf, while failure strain, modulus elasticity and flexural strength decreases. The average highest tensile strength, tensile failure strain, and tensile modulus of elasticity were found being 30.01 MPa at Vf = 40.5%, 0.027 mm/mm atÂ  = 0%, and 1.47 GPa at Vf = 0%, respectively. The average highest flexural strength, failure strain and modulus of elasticity were observed being 153.92 MPa at Vf = 10.7%, 0.0358 mm/mm at Vf = 0%, and 3.242 GPa at Vf =10.7%, respectively. It was observed that specimens were failed by fiber pull out and debonding.